Conformation of the andalusian identity from the discourse. The journal Andalucía during its period of publication in Seville (1916-1917) - Moreno-Pérez, José Luis (Revista de Estudios Andaluces, 2021)
The consolidation of the press as a means of disseminating political ideas and programmes during the first decades of the 20th century verifies the capacity of newspaper sources to study the construction of political identities. This is the case of the journal Andalucía, an organ of Andalusians expression during the regionalist/nationalist stage of historical Andalusianism (1915/1919-1930).